Violence in the Hebrew Bible : Between Text and Reception - Ruiten, Jacques van,; Bekkum, Koert van, (Oudtestamentische Studiën, Old Testament Studies ;, 2020)
In Violence in the Hebrew Bible scholars reflect on texts of violence in the Hebrew Bible, as well as their often problematic reception history. Authoritative texts and traditions can be rewritten and adapted to new circumstances and insights. Texts are subject to a process of change. The study of the ways in which these (authoritative) biblical texts are produced and/or received in various socio-historical circumstances discloses a range of theological and ideological perspectives. In reflecting on these issues, the central question is how to allow for a given text's plurality of possible and realised meanings while also retaining the ability to form critical judgments regarding biblical exegesis. This volume highlight that violence in particular is a fruitful area to explore this tension.